ChemInform Abstract: (3 + 2) Annulation of Amidinothioureas with Binucleophile: Synthesis and Antimicrobial Activity of 3‐Phenylamino‐5‐aryl/alkyl‐1, 2, 4‐oxadiazole Derivatives. Issue 16 (April 2015) - Yerande, Swapnil G.; Ghaisas, Amruta B.; Newase, Kiran M.; Wang, Wei; Wang, Kan; Doemling, Alexander
Abstract 9 Title compounds of type (II) are prepared and tested for their antimicrobial activities.